Educational Technologies and Examination Malpractice in Nigerian Tertiary Education - Omieibi-Davids, Ibiye (Excellencia: International Multi-disciplinary Journal of Education (2994-9521), 2025)
Examinations play a pivotal role in assessing academic achievement, yet their credibility in Nigerian tertiary institutions has been severely undermined by widespread examination malpractice, increasingly enabled by technological devices. This study explores the dual role of educational technologies as both tools for cheating and instruments for enforcing academic integrity. Utilizing a descriptive survey approach, data were collected through eight examination seasons via interviews, informal student conversations, behavioral observations, and document analysis from invigilator reports. Findings revealed diverse forms of malpractice involving digital tools, including smartphones used for real-time information sharing, impersonation facilitated through biometric forgery, and covert communication via social media platforms like WhatsApp. Advanced methods such as microchipping of notes and use of smart devices—watches, glasses, and programmable pens—were also documented. Conversely, technology has shown potential in mitigating malpractice through biometric verification, CCTV surveillance, electronic jammers, and computerized attendance systems. However, limitations such as lack of digital literacy among faculty, insufficient funding, and poor policy implementation hinder effective countermeasures. The study highlights the urgent need for systemic reforms and the strategic application of technological innovations to uphold academic integrity. By presenting both the challenges and potential of educational technologies in combating examination malpractice, this research contributes to the development of sustainable solutions aimed at restoring the value of educational assessments in Nigeria’s higher education system.